Fruits: the flower of commodities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The fruits we eat AusAID CTA SPC co-publication, 2001. 183 pp. ISBN 982 203 802 x CTA number 1072. 20 credit points